MONITORING AKTIVITAS PETANI DAN ANALISIS EKONOMI PERTANIAN SAYURAN ORGANIK DAN KONVENSIONAL PADA DAERAH DATARAN TINGGI BALI - SUDANA, MADE (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 4, No. 3 November2004)
The organic farming company produced yield continuously, weather-independent, the produces in easily to sold at the hotel or supermarket with good price. However, in the organic farming owned personally as well as conventional farming, the production significantly influenced by weather and marketing access to hotel or restaurant is limited. Economic analysis of the three types of agriculture system showed that organic farming with capital intensive as represented by Golden Leaf Farm Company, provide the net revenue Rp. 15.855.750/year/0.1 ha with B/C ratio 3.9; Return on investment (ROI) 290%; net revenue/income ratio (RI) 0.74 and pay back period (PBP) 4 months. In the case of the organic farming which managed personally, produced net revenue Rp. 1.005.762/year/0.1 ha with B/C ratio 1.6, ROI 64%, RI ratio 0.35 and PBP 26 months. On the other hand, in the conventional farming , the net revenue was Rp. 875.200/year/0.1 ha with B/C ratio 1.4, ROI 40%, RI ratio 0.28 and PBP 30 months. In the conventional farming when farmers growing a combination between Vegetables and Potato, the net revenue increased to Rp. 4.577.268/year/0.1 ha with B/C ratio 2.3, ROI 133%, RI ratio 0.54 and PBP 11 months.
Keywords: Mobitoring, Economic Analysis, Organic Farming